2013
DOI: 10.1186/1746-1596-8-37
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated embryonic chondrocyte-expressed gene 1 is associated with hypoxia-inducible factor 1α and Ki67 in human gastric cancer

Abstract: BackgroundGastric cancer is a leading causes of cancer-related deaths ,but the underlying molecular mechanisms of its progression are largely unknown. Differentiated embryonic chondrocyte-expressed gene 1 (DEC1), is an important transcription factor involved in the progression of tumors and has recently been identified to be strongly inducible by hypoxia. Little is known about the contribution of DEC1 to the intracellular hypoxia and proliferation signaling events in gastric cancer.MethodsImmunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…[14,25,26] Here, we solve the complicated problems using propensity score-matched analysis and subgroup analysis. In addition, to further validate the role of Ki-67 expression in EGC, we used the bootstrapping method.…”
Section: Discussionmentioning
confidence: 99%
“…[14,25,26] Here, we solve the complicated problems using propensity score-matched analysis and subgroup analysis. In addition, to further validate the role of Ki-67 expression in EGC, we used the bootstrapping method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the expression of cytokeratin was enhanced in the cells with low oxygen tension [28]. The proliferative cell marker Ki67 is induced under hypoxia conditions in which Ki67 has been found to be highly expressed [17, 29, 30]. Therefore, the expression of HIF-1 alpha, CK20, and Ki67 may be affected by pO 2 levels in the microenvironment of tissues from CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased Plakophilins (PKP2 and PKP3) may be early prognostic markers and loss of PKP3 expression during gastric carcinoma progression may indicate an invasive phenotype [5]. Moreover, the up regulation of differentiated embryonic chondrocyte-expressed gene 1 may play an important role in hypoxia regulation and cell proliferation in gastric cancer [6]. The detection of Ezrin expression can be used as a marker for early diagnosis and prognosis of gastric adenocarcinoma [7].…”
Section: Introductionmentioning
confidence: 99%